The Mediator Effect of Meaningfulness on the Relationship Between Schizotypy Traits and Suicidality - Li, Shu-bin; Liu, Ding; Zhang, Xiao-yuan; Zhao, Jiu-bo (Frontiers in Psychology, 2020)
Introduction: Previous studies have found that schizotypy can predict suicide, and that meaningfulness has influential effects on suicidality in the general population. However, it is still not clear whether meaningfulness is associated with suicidality in individuals with schizotypy. The aim of this study was to assess the mediating effects of meaningfulness in the relationship between schizotypy and suicidality. Method: We recruited 2,615 university students (including undergraduates and postgraduates; mean age = 18.35, SD = 0.81; males, 39%) to participate in our study, and used the Meaningful Life Measure (Chinese, revised) to assess their experiences of meaningfulness, the Suicidal Behaviors Questionnaire (Chinese version) to evaluate participants’ suicidal thoughts and attempts, and the Schizotypal Personality Questionnaire to examine their personal schizotypal traits. Results: Meaningfulness was found to be inversely related to the other two factors, and schizotypy was positively associated with suicidality. The correlation between schizotypy and suicidality was reduced when meaningfulness was included, which may suggest that meaningfulness can partly mediate this relationship, accounting for 55.47% of the association. Conclusions: Prior research has suggested that assessing meaningfulness could provide more detailed information about suicide risk in individuals with schizotypy. Our study found that improving perceptions of meaningfulness can be an effective intervention in reducing suicide risk among people with schizotypy.